Amadeusz’s Prosper: Effective Reintegration of Adults Facing Firearm-Related Charges in Ontario, Canada - Eizadirad, Ardavan; Chambers, Tina Nadia; Brown, Sheena Blake (Advances in Social Sciences Research Journal, 2024)
This study evaluates the impact of Amadeusz’ Prosper program which supports individuals with firearm-related charges between the ages of 18 to 29 in Ontario, Canada. Prosper offers intensive case management through caseworkers who co-create tailored support plans with participants based on their immediate needs and long-term goals. The program supports individuals during incarceration and post-release once back in community. This study engaged 44 participants through interviews conducted between October 2022 and April 2023. Participants included program beneficiaries (n=29), family members (n=8), community partners (n=4), and caseworkers (n=3). Intersectionality and Critical Race Theory paradigms were applied as part of data analysis to uncover the program’s impact, strengths, and barriers in implementation. Results showed a correlation between the program and positive outcomes in personal development, well-being, and reintegration of participants. Overall, the study contributes to filling in the research gap offering nuanced insights into how to support individuals with firearm-related charges in Canada as part of offering more effective reintegration supports and reducing recidivism.